CSR collaboration in multi-level supply chains: a conceptual model. Issue 2 (3rd April 2017) - Vo, Thi Le Hoa; Nguyen, Thi Lan Anh
ABSTRACT: This paper aims to study the role of supply chain (SC) collaboration in improving the performance of corporate social responsibility (CSR) implementation in a multi-level supply chain. By using a system dynamics approach, it attempts to find out the best form of CSR collaboration for a sustainable supply chain. The results show that SC collaboration via three sharing schemes – resources-sharing, cost-sharing and profit-sharing – plays a decisive role for efficient CSR implementation by improving the interests of individual members and the whole supply chain as well. This work allows the authors not only to have more insights into determining the best strategies to implement CSR in the supply chain but also to propose important solutions to build and boost supply chain management.